Gambaran Sleep Hygiene dan Kualitas Tidur Orang dengan HIV (ODHIV) di Kelompok Dukungan Sebaya (KDS Arjuna) Semarang - Nia Julian Wati; Ahmad Ikhlasul Amal (An-Najat, 2025)
Sleep quality disorders usually occur in people with psychological and physiological disorders, including people living with HIV (PLHIV). Disrupted sleep quality generally occurs when a person’s sleep and rest patterns are disturbed. Decreased and poor sleep quality will affect a person’s functional status and health. Several factors that can influence sleep quality in PDHIV are mental health factors, anxiety, consumption of ARV drugs and sleep hygiene habits. This study aims to describe sleep hygiene and sleep quality among PLHIV at KDS Arjuna Semarang. This research uses a quantitative descriptive research design. A total of 70 respondents were obtained using consecutive sampling techniques. The research results showed that the majority of PLHIV were female, namely 46 respondents (65.7%), the youngest age was 19 years, and the oldest age was 45 years, the majority were married, namely 40 respondents (57.1%), who had a high school education. /SMK amounted to 40 respondents (57.1%), the majority of jobs were private employees, amounting to 48 respondents (68.8%). The research results show that the sleep hygiene of people living with HIV (PLHIV) at KDS Arjuna Semarang is that 47 respondents (67.1%) have good sleep hygiene and 2 respondents (2.9%) PLHIV have poor sleep hygiene. The sleep quality of people living with HIV (PLHIV) at KDS Arjuna Semarang, namely 37 respondents (52.9%) had good sleep quality, and 33 respondents (47.1%) had poor sleep quality. Suggestions for nurses to provide education regarding the importance of health services in providing nursing care, compliance with taking medication, and motivating PLHIV to have good sleep hygiene.